Investigation of immunomodulatory effects of phytosterols isolated from Clinacanthus nutans - Liew, Crystal Xiao-Qi (2025)
Clinacanthus nutans (Burm. F.) Lindau, a traditional medicinal plant from the Acanthaceae family used in Southeast Asia to treat fever, skin rashes, viral infections, and insect bites. The plant is known for its anti-cancer, antimicrobial, anti-herpes simplex virus, antioxidant, and anti-inflammatory properties. Recent studies have reported on the immunomodulatory properties of C. nutans. However, most research to date has focused on crude extracts rather than purified compounds. This study aims to investigate the immunosuppressive effects of beta-sitosterol, stigmasterol, and shaftoside, isolated from C. nutans, in female C57BL/6 mice. Preliminary in vitro studies in Jurkat cells revealed that beta-sitosterol and stigmasterol shaftoside showed lower IC50 values than shaftoside and exhibited dose-dependent cytotoxicity in 3-(4,5-dimethylthiazol-2-yl)-2,5 diphenyl tetrazolium bromide (MTT) assay. All three compounds did not affect the lymphocytes proliferation in bromodeoxyuridine (BrdU) assay in vitro. Enzyme-linked immunosorbent assay (ELISA) showed that shaftoside possibly reduced Th2 cytokine IL-4, promoted anti-inflammatory IL-10 cytokine. Conversely, beta-sitosterol may stimulated Th1 cytokine IFN-γ while inhibiting Th2 cytokine IL-4, suggesting a Th1 bias, while stigmasterol demonstrated decrease in both Th1 and Th2 cytokines. Subsequent in vivo experiments in C57BL/6 mice orally administered with C. nutans isolated compounds provided more information on the immunosuppressive activity. Shaftoside reduced B and T lymphocytes proliferation, with suppression of Th1 (IFN-γ, IL-2) and Th2 cytokines (IL-4), while maintaining IL-10 production, Shaftoside also exhibited an increase in total IgG and suppressed IgM antibody production. Fluorescence-activated cell sorting (FACS) analysis indicated that shaftoside reduced populations of CD19+ B cells, CD3+ T cells, CD4+ T helper cells and CD8+ T cytotoxic cells. Beta-sitosterol and stigmasterol also demonstrated similar suppression in B and T lymphocytes proliferation and stimulated Th1 cytokines (IFN-γ, IL-2) dose-dependently but showed no significant impact on Th2 (IL-4, IL-10) cytokines. Both phytosterol compounds notably reduced CD4+ T helper cells while also decreasing CD19+ B cells, CD3+ T cells and CD8+ T cytotoxic cells. C57BL/6 treated mice were also challenged with a Cryptosporidium parvum infection model. Beta-sitosterol was discovered to induce immunosuppression with less severe tissue damage in the terminal ileum and liver compared to stigmasterol, shaftoside, and the control drug dexamethasone, while exhibiting higher oocyst shedding intensity, second only to dexamethasone. The challenge study results suggest beta-sitosterol could serve as a more tolerable natural alternative to synthetic immunosuppressive agents like dexamethasone. In conclusion, this study demonstrated the immunosuppressive potential of beta-sitosterol, stigmasterol, and shaftoside especially in conditions characterised by Th2 dominance, such as asthma and allergic diseases. In future perspective, beta-sitosterol, stigmasterol, and shaftoside could be potentially developed as naturally derived immunotherapeutic agents with less adverse effects.